Épocas de colheita, armazenamento e superação de dormência em sementes de capim-buffel (Cenchrus ciliaris L.) - Silva, Jamille Cardeal da (2022)
The low supply of forage to the herds in the estimation periods has been a great challenge in the northeastern semi-arid region, generating a direct impact for producers in this region. The buffel grass is a grass that presents an excellent adaptation to the soil and climate conditions because it has great resistance to periods of drought. The objective of this work was to evaluate the solution and overcoming of dormancy in C. ciliaris seeds. Experimental design was used both completely randomized (DIC) for selected seeds - 6 x and freshly harvested seeds - scheme 14 and two solutions of embition, water / nitrate of potentially 14, water / nitrate of potentially. six lots of two cultivars and two imbibition solutions, water/potassium nitrate), respectively. 4 years harvested from the cold chamber (1012°), belonging to the Semiarid Cenchus Bank. Seeds from crops or crops from different crops were made in 2019 and sustain in crops and crops harvests according to the year 2019 harvest period. Analyzed data was analyzed for verification of data analysis data . The adjustment procedure using Generalized Linear Models (GLM) was applied. MLG analysis analysis were made as significant differences within each accession, test and measurement comparison data, by means of statistical treatment %R. Relevant effect (p < 15) for all traits0, differently germination and relative germination. For the newly harvested seeds, according to the analysis of variance, a significant difference (p < 0.05) between the treatments used to overcome the dormancy of buffel grass seeds, in relation to seed germination. Note that ARIDUS accessions harvested at different times of the year were the ones that provided the greatest amount of germination water when treated with distilled water. It is concluded that the quality of adjustment of the seeds may have quality of the same, but that quality of quality of the same. The use of unaccepted KNO3 to overcome the dormancy of newly harvested seeds.